Identifying impaired mental health in patients with type 2 diabetes: a cross-sectional study in general practice - Line T Jakobsen; Anne Søjbjerg; Stinne E Rasmussen; Kaj S Christensen (BJGP Open)
Background: Type two diabetes (T2D) is linked to impaired mental health. International guidelines emphasise the importance of including psychological aspects in diabetes care. Yet, no systematic approach has been implemented to assess mental health in patients with T2D in general practice. Aim: To evaluate the mental health of patients with T2D in general practice, and to investigate the effectiveness of asking patients about their wellbeing by using a single-item question compared with the five-item World Health Organization-Five Wellbeing Index (WHO-5). Design & setting: A cross-sectional study was undertaken, which included 230 patients with T2D in Danish general practice, from 1 May 2023–31 January 2024. Method: Eligible patients were recruited at the annual chronic care consultation. They answered a single-item question on wellbeing and four validated measures of general wellbeing (WHO-5), depression (Patient Health Questionnaire-9; PHQ-9), anxiety (Generalised Anxiety Disorder-7; GAD-7), and diabetes distress (Problem Areas in Diabetes-5; PAID-5). Results: Overall, 32% of patients expressed symptoms of impaired mental health. Notably, the WHO-5 identified 53% of these patients, whereas only 12% of patients were identified through the single-item question. Importantly, among the patients exhibiting symptoms of impaired mental health, those identified by the WHO-5 displayed statistically significantly lower mental health scores across all measures (except PAID-5) compared with those not identified by the WHO-5. Conclusion: A significant proportion of patients with T2D in general practice are affected by mental health issues. Our findings indicate that a single-item question may not sufficiently detect these issues, highlighting the importance of incorporating tools, such as the WHO-5, to offer a more comprehensive approach in diabetes care.